Negotiating Presence: The Dynamics of Passive Representation Among Ultra‐Orthodox Women in Public Organizations - Maayan Davidovitz; Rachel Gali Cinamon (Public Administration, 2026)
ABSTRACT Studies in representative bureaucracy have focused on whether passive representation translates into active representation. We shift this analytical lens by conceptualizing passive representation not as a static demographic condition or a preliminary stage, but as a dynamic organizational process. Drawing on 15 in‐depth interviews and a focus group with 14 ultra‐Orthodox women serving in mid‐ and senior‐level public positions in Israel, we examine how passive representation is enacted, negotiated, and gradually institutionalized in male‐dominated settings. Findings show how women's underrepresentation structures their entry and advancement through informal expectations and gendered networks, and how women “negotiate presence” by building legitimacy through heightened professionalism, creative networking in the face of gender segregation, and strategic engagement with supportive leaders. Through mentoring and gate‐opening practices, our participants created ripple effects that increased access for others over time. We argue that passive representation is a relational and evolving mechanism shaped by role interpretations and organizational constraints, reshaping access and participation even without formal policy changes.